2021
DOI: 10.1186/s12884-021-03730-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gestational diabetes mellitus diagnosed during the third trimester on pregnancy outcomes: a case-control study

Abstract: Background In 2010, the International Association of Diabetes and Pregnancy Study Group (IADPSG) proposed new criteria indicating that gestational diabetes mellitus (GDM) can be diagnosed if the fasting threshold of ≤92 mg/dL, 1-h threshold of ≤180 mg/dL, or 2-h threshold of ≤153 mg/dL are exceeded during the 75-g 2-h oral glucose tolerance test (OGTT) performed at 24–28 weeks of gestation. The World Health Organization (WHO) recommends using the proposed diagnostic threshold values of the IADP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…[17][18][19]23,24 Heterogeneity of population characteristics was considerable between the studies. This was evident by the inclusion in several studies, of women with polyhydramnios, 10,19,21,22,24 suspected LGA/macrosomia, 10,17,[20][21][22]24 glycosuria, 10 and risk factors for GDM such as obesity and family history of diabetes. 16,24,25 The characteristics of the studies included are shown in Table 1.…”
Section: Methods For Late Gdm Diagnosis and Time Of Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19]23,24 Heterogeneity of population characteristics was considerable between the studies. This was evident by the inclusion in several studies, of women with polyhydramnios, 10,19,21,22,24 suspected LGA/macrosomia, 10,17,[20][21][22]24 glycosuria, 10 and risk factors for GDM such as obesity and family history of diabetes. 16,24,25 The characteristics of the studies included are shown in Table 1.…”
Section: Methods For Late Gdm Diagnosis and Time Of Diagnosismentioning
confidence: 99%
“…The 12 studies that were selected for the meta-analysis included 3103 women and 3674 pregnancies (571 pregnancies with late GDM and 3103 pregnancies without late GDM) (Figure 1). 9,10,[16][17][18][19][20][21][22][23][24][25] Table S4 presents the quality and risk of bias assessment of the included studies. 14 Eleven of the F I G U R E 2 Forest plots and summary of odds ratios of associations between late gestational diabetes and perinatal outcomes.…”
Section: Maternal Age Y Gdm Versus Non-gdm Bmimentioning
confidence: 99%
“…[11][12][13] Usually, late OGTT is performed based on clinical findings such as polyhydramnios or a suspected LGA fetus. 13,14 A recent study reported a late GDM diagnosis rate of 22% (>29 weeks), of whom 36.8% were with third trimester BMI > 30 kg/m 2.12 Another study showed associations of abnormal nearterm OGTT with both maternal and neonatal complications, and recommended that late third-trimester OGTT should be considered for the subset of women with suspected LGA fetuses or polyhydramnios. 15,16 However, only a few studies controlled for BMI in the late third trimester and examined its association with late GDM diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the implications of late GDM diagnosis (>29 weeks) 11–13 . Usually, late OGTT is performed based on clinical findings such as polyhydramnios or a suspected LGA fetus 13,14 . A recent study reported a late GDM diagnosis rate of 22% (>29 weeks), of whom 36.8% were with third trimester BMI > 30 kg/m 2.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the implications of late GDM diagnosis [14][15][16], when an oral glucose tolerance test (OGTT) is performed beyond the recommended 24-28 weeks gestation. Usually, late OGTT is performed based on clinical ndings such as polyhydramnios or a suspected LGA fetus [16][17]. A recent study reported a late GDM diagnosis rate of 22% (> 29 weeks), of whom 36.8% were with BMI > 30 kg/m 2 [15].…”
Section: Introductionmentioning
confidence: 99%